Evaluating the quality of aquatic environment on the Planktonic-Index of Biotic Integrity (P-IBI) based whiteleg shrimp Litopenaeus vannamei (Boone, 1931) ponds - MUHAMMAD AKBARURRASYID; VINI TARU FEBRIANI PRAJAYATI; ACHMAD SOFIAN; MUSTIKA KATRESNA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Akbarurrasyid M, Prajayati VTF, Sofian A, Katresna M. 2023. Evaluating the quality of aquatic environment on the Planktonic-Index of Biotic Integrity (P-IBI) based whiteleg shrimp Litopenaeus vannamei (Boone, 1931) ponds. Biodiversitas 24: 4845-4853. Plankton is one of the biotic indicators used to evaluate the quality of the aquatic environment in the ponds. This study aims to find out the quality of the aquatic environment of the whiteleg shrimp Litopenaeus vannamei (Boone, 1931) ponds using Planktonic-Index Biotic of Integrity (P-IBI). Samples were collected in intensive L. vannamei farming in Pandeglang, Banten, and analyzed by the P-IBI method using 4 categories and 35 attributes. Matrix attributes include community composition, number of species, species density and species diversity. The P-IBI value is compared with the assessment category to obtain the status of aquatic environmental quality. The environmental quality assessment categories are: very good (83-100%), good (73-82%), moderate (57-72%) and bad (0-56%). The results of the study showed the assessment of Community Composition (CC) of 66 (66%) and the scoring of Amount of Species (AS) of 65 (59.09%) on the attributes of the number of Bacilloryophycea, percentage of Cyanophycea, Dinophyceae, and Protozoa. The scoring of Species Density (SD) obtained 65 (59.09%) on attributes of the abundance of Chlorophyceae and Bacilloryophycea and the low abundance of Dinophyceae and Protozoa. Meanwhile, the scoring of Species Diversity (SDI) obtained a maximal score of 30 (100%), which showed that the species diversity of plankton based on the Shannon-Wiener Index (H'), Margalef Index (E), and Pielou Index (D) was still in good condition, the species diversity was stable, and there were no dominating species. The P-IBI score obtained was in the moderate category for L. vannamei farming activities.